BULGARIAN PASSPORTS, MACEDONIAN IDENTITY THE INVENTION OF EU CITIZENSHIP IN THE REPUBLIC OF MACEDONIA (ЕтноАнтропоЗум, 2014)
My concern here is with ethnic Macedonians, especially youth, who claim not to be interested in whether it is ideologically appropriate or inappropriate to apply for Bulgarian passports, but rather point to the practical and economic benefits that Bulgarian passports carry for their holders – mainly freedom to travel without a visa within the EU and access to a greater number of choices in their lives. The case of Macedonia, therefore, helps us view identification documents as objects that neither necessarily fix nationality nor are ineluctable guarantees of belonging to the (Bulgarian) nation-state, and understand state documentation practices are practices that do not always produce determined identities and citizen-subjects.